PENGARUH JENIS DAN DOSIS PUPUK ORGANIK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TERUNG (Solanum melongena L.) VARIETAS MUSTANG F-1 - Muhammad Safei, Abdul Rahmi, dan Noor Jannah (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2014)
Objectives of the research were: (1) to study the effect of kind and dosage Organic fertilizer, as well as their interaction on the growth and yield of eggplant; (2) to find kind and profer dosage of organic fertilizer for better growth and yield of eggplant.   The research was carried out from February to May 2013, since preparation of growing media until crop harvested. It was held at Purwodadi Urban Village, Linggang Bigung Sub-District, West Kutai District.  The Completely Randomised Design was employed for this research with factorial 2 x 5 and 4 replications.  The first factor was kind of organic fertilizer (P) that consisted of 2 levels: cow manure fertilizer (p1), and bokashi of cow manure fertilizer (p2).  And the second factor was dosage of organic fertilizer (D) that consisted of 2 levels: no organic fertilizer (d0),  2,50 Mg ha-1 equal to 18,75 g polybag-1 (d1);  5,00 Mg ha-1 equal to 37,50 g polybag-1 (d2);  7,50 Mg ha-1 equal to 56,25 g polybag-1 (d3); and 10,00 Mg ha-1 equal to 75,00 g polybag-1 (d4).  Results of the research revealed that: (1) the kind of organic fertilizer affected significantly to very significantly on the plant height at 45 days after planting, length of fruit, and diameter of fruit, while no significant on the  the plant height at 15 and 30 days after planting,  number of leaf at 15, 30, and 45 days after planting,  days of crop flowered, days of crop harvested, number of fruit per crop, and fruit weight per crop.  The weighest fruit was attained by bokashi of cow manure fertilizer (p2), namely 0,74 kg per crop, whereas the lightest one was by cow manure fertilizer (p1) with only 0,72 kg per crop; (2) the organic fertilizer dosage affected significant until very significantly on the  plant height at 30 and 45 days after planting, number of leaf at 45 days after planting,  days of crop flowered, days of crop harvested, number of fruit  per crop, length of fruit, and fruit weight per crop; but no significant on the  the plant height at 15 days after planting, number of leaf at 15 and 30 days after planting,  and diameter of fruit. The weighest fruit was attained by 75,00 g polybag-1 treatment (d4), namely 0,85 kg per crop and the lightest one was by no organic fertilizer application treatment (d0) with only 0,66 kg per crop; and (3) the interaction between those two factors no significant on the all parameters, exceptly on the plant height at 30 days after planting.